2018
DOI: 10.1080/2162402x.2017.1412901
|View full text |Cite
|
Sign up to set email alerts
|

Survival gain in glioblastoma patients treated with dendritic cell immunotherapy is associated with increased NK but not CD8+ T cell activation in the presence of adjuvant temozolomide

Abstract: In a two-stage phase II study, 24 patients with first diagnosis of glioblastoma (GBM) were treated with dendritic cell (DC) immunotherapy associated to standard radiochemotherapy with temozolomide (TMZ) followed by adjuvant TMZ.Three intradermal injections of mature DC loaded with autologous GBM lysate were administered before adjuvant TMZ, while 4 injections were performed during adjuvant TMZ. According to a two-stage Simon design, to proceed to the second stage progression-free survival (PFS) 12 months after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
61
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(69 citation statements)
references
References 38 publications
6
61
0
2
Order By: Relevance
“…Oncolytic viruses targeting DIPG have also begun clinical trials 43 and NK cells have been shown to be involved in the immune response to lysed tumor cells in the brain 44 . We did not yet test synergy of NK cells with standard-of-care radiotherapy or chemotherapy in our models, which is warranted based on pre-clinical 45,46 and clinical trial 47 data of adult gliomas.…”
Section: Discussionmentioning
confidence: 99%
“…Oncolytic viruses targeting DIPG have also begun clinical trials 43 and NK cells have been shown to be involved in the immune response to lysed tumor cells in the brain 44 . We did not yet test synergy of NK cells with standard-of-care radiotherapy or chemotherapy in our models, which is warranted based on pre-clinical 45,46 and clinical trial 47 data of adult gliomas.…”
Section: Discussionmentioning
confidence: 99%
“…Low-dose chemotherapy also increases the influx of CD8 T cells into the tumor in pre-clinical models of glioblastoma [89], but the peripheral lymphodepletion in patients treated with chemotherapy may counteract these beneficial effects [79]. Additionally, TMZ administration has been shown to have a detrimental effect on the formation of a memory CD8+ T cell response against glioblastoma [90]. This makes (low dose) chemotherapy unlikely to be an attractive sensitizer for anti-glioblastoma T cell treatment.…”
Section: Increasing the Cd8 T Cell Influxmentioning
confidence: 99%
“…In the University of Navarra phase II trial, autologous DC vaccines were administered to 31 patients who had a median OS of 23.4 months [90] . The high grade glioma-2006 phase I and II trials administered autologous DC vaccines to 77 patients in total with a median OS of 19.4 months [91] , and the phase II DENDR1 trial administered autologous tumor lysate vaccines to 24 patients demonstrated a median OS of 20.1 months [92] . Compared to the 14 months OS following GBM diagnosis and standard of care, DC vaccines pulsed with autologous tumor lysate have demonstrated a substantial and consistent increase in OS, with little to no adverse events.…”
Section: Vaccinesmentioning
confidence: 99%
“…Trials have shown mixed results as to whether or not DC vaccines increase cytotoxic T-cell and TH1 responses, which is further confounded by trials that did not measure these criteria. Trials that have measured NK cell populations have shown that an increase in NK cell activity and number following vaccinations has been correlated with improved outcomes [86,92] . In order to improve the development of DC vaccinations, consistent immunological evaluations (patient T-cell, NK cell, and cytokine production, etc.)…”
Section: Vaccinesmentioning
confidence: 99%